Persebaran struktur geologi dan batuan pra-tersier pada Pulau Bangka bagian utara - Rezki Naufan Hendrawan; Benyamin Sapiie; Nurcahyo Indro Basuki (Journal of Science, Technology, and Visual Culture, 2021)
Northern Bangka Island composed by Permian Pemali Metamorphic Complex and Late Triassic – Early Jurassic S-type Klabat Granite. Tectonic phase of Northern Bangka Island indicated a similar pattern with Bentong-Raub Suture Zone in Peninsula Malaysia. Suture Zone marked by several kind of metamorphic rocks and granites with different lithology. The research used random sampling field observation to find structural data and fabric element of rocks. Pre-Tertiary rocks in Northern Bangka Island consist of quartz schist, mica phyllite, granodiorite, granite, sandstone, and conglomerate. That rocks commonly record lineation, foliation, S-C fabric, fold, fault, and joint as kinematic indicator.